Uniqueness and status consumption: how luxury goods companies entice the young - Marchegiani, Chris; Latter, Chelsey (School of Marketing, Curtin Business School, 2009)
This paper identifies the key antecedents and moderators with regard to willingness of consumers in the purchase of an haute couture luxury apparel brand and it?s ready to wear line. The objective of this paper is to develop a conceptual framework based on the research gaps highlighted in the literature review. The research objectives are discussed along with the theoretical background of the constructs. From here the relevant literature is used to support the development of the research model and the hypothesised relationships.